THE IMAGE OF PRINCE GEBANG IN BABAD SUTAJAYA MANUSCRIPT - Anwar Sanusi; Tendi Tendi (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2019)
Prince Gebang was one of the local rulers who collaborated with the VOC at the end of the 17th century. His domain, named as the Principality of Gebang (Kepangeranan Gebang), extended from the northern coastal area of Gebang Sea to the south side of the Cijolang River bordering on Galuh. Although the name of Sutajaya was clearly written as Prince Gebang (Pangeran Gebang) in the colonial archives, but his identity and his travel process towards the power of the Gebang area was not clearly explained. This article aimed to reveal the image of Prince Gebang through Babad Sutajaya manuscript stored in Pangeran (Prince) Pasarean Museum. Based on the ancient manuscripts, a number of essences related footage Sutajaya figure were taken to be analyzed. Historical elements contained in the affinity of the story were comparated to records of colonial archives and sources of oral traditions that still exist. From this study, it is known that Babad Sutajaya depicts the image of Prince Gebang as an important figure, who came from the royal court of Cirebon. In addition, this manuscript also illustrates Prince Gebang’s abilities and reveals how he gained the territory of Gebang as his controlled area.Keywords: Image, prince sutajaya, principality of gebang, babad, Royal Court of Cirebon